Do Educational Paradigms Influence Students’ Motivation to Study History? - I. V. Tsvetkova (Высшее образование в России)
The article highlights the features of three paradigms of education: competency-based, digital and modernization. The purpose of the study is to analyze the influence of factors of educational paradigms on the motivation of students to study history at a university. The empirical base of the study includes materials from an Internet survey of first- and second-year students of universities in Samara region (N=389) conducted in 2022. Depending on the attitude of students to the study of history at the university, three groups of respondents were identified: “supporters”, “moderate supporters” and “indifferent to the study of history at the university”. The grouping of students made it possible to analyze the differentiated influence of the factors of three types of educational paradigms on the motivation of students. The modernization paradigm has the greatest positive potential in shaping the motivation of students to study history. It, to a greater extent than other paradigms, takes into account the specifics of history as a humanitarian discipline. Within the framework of three paradigms, factors that have a negative impact on the motivation of students to study history are identified. Among them, insufficient development of independent work skills is of great importance. The practical significance of the study is to use the information obtained to improve the methods of teaching history at the university, as well as other social and humanitarian disciplines, taking into account the factors of student motivation.